Isomeric cues direct macrocycle selection from complex chemical systems for selective separation and recycling - Wang, Xin; Yang, Jinghui; Rosqvist, Emil; Lyu, Yonglei; Papageorgiou, Anastassios C.; Peltonen, Jouko; Mäkilä, Ermei; Cheng, Fangyi; Li, Jianwei (Cell Press, 2026)
Living systems translate subtle molecular variations into functional complexity through selective recognition and hierarchical self-assembly. Here, we report that dynamic combinatorial chemistry (DCC) can amplify minute structural differences among isomeric templates, guiding templated selection toward distinct supramolecular outcomes. Using a dithiol building block, a library of macrocycles is generated, within which only one isomeric template selectively amplifies the tetrameric macrocycle. Their co-assembly produces highly ordered 2D nanosheets that spontaneously precipitate, enabling facile component separation. This selective organization contrasts with the simple 1:1 complex formed by other isomers, underscoring the sensitivity of dynamic systems to small structural cues. Significantly, both the template and the amplified species are recovered with high efficiency, allowing material recyclability. These findings reveal how dynamic molecular systems transform subtle information into functional architectures, offering a conceptual model for templated selection and a strategy for the design of adaptive supramolecular materials featuring selective recognition, separation, and reuse.